Adaptation and Validation of Addenbrooke's Cognitive Examination-III in Bengali for Screening MCI and Dementia. (2nd July 2022) - Bhattacharyya, Bidisha; Mukherjee, Ruchira; Mukherjee, Adreesh; Das, Gautam; Dogra, Atanu Kumar; Das, Sujata; Biswas, Atanu
Abstract: Objective: Bengali, the 6th most spoken language globally with 268 million speakers, demands a culturally appropriate tool for screening any cognitive compromise in this population. Addenbrooke Cognitive Examination-III (ACE-III) is a standardized tool used for screening and/or diagnostic purpose worldwide. The aim of the present study was to adapt and validate ACE-III into Bengali language. Methods: The ACE-III UK Version A (2012) was adapted with linguistically and culturally appropriate items and validated on Bengali speakers. The participants consisted of 40 dementia and 22 Mild Cognitive Impairment (MCI) patients and 120 healthy-controls. Reliability and validity were examined. Discriminant function analysis was done. Sensitivity and specificity were evaluated and optimum cut-offs were established for MCI and dementia. Results: Both sensitivity and specificity of ACE-III-Bengali of identifying dementia was 1; sensitivity for MCI ranged from 0.83 to 1, specificity from 0.76 to 1. Discriminant function analysis showed a significant difference in all domains of ACE-III-Bengali between healthy individuals and persons with neurocognitive impairment. Separate optimum ACE-III-Bengali cut-off scores were established according to level of education. For low education (<Class 10) cut-off was 83 for dementia and 86 for MCI, whereas, for high education (≥Class 10) it was 85 and 88 for dementia and MCI, respectively. The area under curve for distinguishing dementia and MCI ranged from 0.949 to 0.955. Conclusion: The ACE-III-Bengali is found to have high diagnostic accuracy in identifying dementia and MCI in the Bengali population.